Are educational transitions related to young people’s loneliness and mental health: a systematic review - Amanda Jasmin Emilia Sundqvist; Jessica Hemberg; Pia Nyman-Kurkiala; Ottar Ness (International Journal of Adolescence and Youth)
Transitions can be described as passage/movement from one life phase, condition, or status to another, where people learn to adapt to the change through inner reorientation, adaptation, and/or transformation. The aim was to explore whether educational transitions during adolescence and emerging adulthood relate to loneliness and mental health. A systematic review was conducted. A total of 32 articles were included. Educational transitions were associated with both positive and negative outcomes. Individual variables might impact how a transition is experienced. To alleviate negative outcomes for young people, social support and targeted interventions should be developed, and support made available and accessible. Interventions should focus on preventing disruptions in social networks and increasing connections and collaborations between support networks across each educational stage. Future research should examine how interventions can support individuals who are negatively affected by educational transitions.